2018 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2018
DOI: 10.23919/date.2018.8342059
|View full text |Cite
|
Sign up to set email alerts
|

A high-speed design methodology for inductive coupling links in 3D-ICs

Abstract: Inductive coupling links (ICLs) are gaining traction as an alternative to through silicon vias (TSVs) for 3D integration, promising high-bandwidth connectivity without the inflated fabrication costs associated with TSV-enabled processes. For power-efficient ICL design, optimisation of the utilised physical inductor geometries is essential, however typically necessitates the use of finite element analysis (FEA) in addition to manual parameter fitting, a process that can take several hours even for a single geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…When combining these parameters (R, L, C, and M) to evaluate efficiency, the combined average error was determined to be 7.8%. This represents a 1.17× improvement upon the expressions used in [10].…”
Section: Empirical Expression Evaluation 1) R L and C Extractionmentioning
confidence: 95%
See 1 more Smart Citation
“…When combining these parameters (R, L, C, and M) to evaluate efficiency, the combined average error was determined to be 7.8%. This represents a 1.17× improvement upon the expressions used in [10].…”
Section: Empirical Expression Evaluation 1) R L and C Extractionmentioning
confidence: 95%
“…Considering the inductor in this way facilitates more accurate evaluation than the use of single expressions and allows for accurate evaluation of the nonuniform inductors proposed in this paper. The use of this improved scalable inductor model in COIL-3-D is supplementary to [10].…”
Section: A Scalable Inductor Modelmentioning
confidence: 99%
“…The popularity of these three approximation formulas is quite distinct. From the research works found in the literature, it is possible to state that the Current Sheet Approximation formula is the most used [8,[19][20][21][22][23][24]37,38], followed by the Modified Wheeler [24,30] and the Data Fitted Monomial [26,39].…”
Section: Review Of Analytical Modelsmentioning
confidence: 99%
“…The second element in the CoDAPT architecture is the inductive coupling channel itself, consisting of two coupled planar inductors. Power transmission between two stacked inductors is optimised when their layouts are congruent [11]. Therefore, two congruent square spiral inductors are considered in this paper (as square inductors offer the highest inductance per unit area [12]).…”
Section: B Inductive Channel Designmentioning
confidence: 99%